SURGICAL MANAGEMENT OF OSTEOCHONDRITIS DISSECANS OF THE ELBOW IN CHILDREN: IS THERE CONSENSUS AMONG EXPERTS?. Issue 4 (28th April 2020) - LaValva, Scott M.; Talathi, Nakul S.; Patel, Neeraj M.; Edmonds, Eric W.; Ellis, Henry B.; Fabricant, Peter D.; Lyon, Roger; Milewski, Matthew D.; Polousky, John; Shea, Kevin G.; Wall, Eric J.; Wilson, Philip; et al.
Background: Although the available evidence generally supports surgical treatment of unstable osteochondritis dissecans (OCD) lesions of the elbow, the optimal surgical management lacks consensus. Given the myriad of options available for skeletally immature patients, the purpose of this study was to identify preferred surgical procedures based upon patient and OCD characteristics among a group of high volume surgeons. Hypothesis/Purpose: To understand current treatment practices for experts on OCD of the elbow. Methods: A survey evaluating the surgical treatment strategies for twenty-three clinical vignettes of skeletally immature patients with OCD of the elbow was created and distributed electronically to members of the Research on Osteochondritis Dissecans (ROCK) study group using REDCap. Each vignette described an OCD lesion of varying location, size, degree of cartilage involvement, and depth. Multiple-choice answers related to specific treatment strategies and technique were provided for each lesion. Standard descriptive statistics were used to summarize and compare responses for each vignette. Results: Fifteen surgeons treating OCD of the elbow participated in the study. All respondents were attending-level surgeons. One-third of responding surgeons treat elbow OCD weekly, 53% monthly, and 13% every six months. In skeletally immature patients with stable, intact elbow OCD lesions, 80% of surgeons would treat with transarticular (58%), retroarticular (33%), or combined trans/retroarticular (8%) drilling. For full-thickness (FT) osteochondral defects occupying 33% or 66% of capitellar width, the preferred treatment modality varied substantially based on lesion depth. Overall, the preferred strategies for these lesions were (1) debridement with marrow stimulation for FT defects with 1-2 mm subchondral bone loss and (2) internal fixation for trap-door lesions with either trace or > 4 mm of subchondral bone. There was substantial heterogeneity with respect to treatment strategy for FT defects with > 4 mm bone loss. For a lesion occupying 33% of capitellar width, 47% of surgeons would treat with debridement and marrow stimulation, 47% would treat with an osteochondral transfer, and 6% would perform both. For larger lesions of 66% width, slightly more would treat with osteochondral transfer (47% vs. 40%). Ultimately, > 75% agreement was only reached in 19% of the vignettes, highlighting the high degree of variability in the treatment of elbow OCD. Conclusion: For elbow OCD in skeletally immature patients, the greatest agreement exists for (1) the drilling of stable OCD lesions, though there is variability with respect to technique (transarticular/retroarticular/combined) and (2) internal fixation for trap-door lesions with > 5mm of subchondral bone. Nonetheless, high-quality clinical data to guide decision-making is currently lacking for capitellar OCD. Even among a group of experienced experts, there is significant disagreement regarding preferred surgical methods. Our study ultimately highlights the need for multicenter, prospective investigations to evaluate the clinical outcomes of various treatment strategies for OCD of the elbow. : Table I. Preferred intra-operative treatment principles and techniques for a central, full-thickness OCD lesion of the capitellum. Lesion Depth Treatment Principle % of Surgeons Central, Contained 33% Width of Capitellum Full-Thickness Defect 4 mm Bone Loss Transarticular/Retroarticular Drilling 0 Debridement +/- Marrow Stimulation 46.7 Debridement Only 0 Debridement + Marrow Stimulation 100 Drilling of Full-Thickness Defect 28.6 Awl 42.9 Abrasion 14.3 Other 14.3 Internal Fixation 0 Osteochondral Transfer 46.7 Allograft 28.6 Autograft 71.4 Biopsy and ACI 0 Figure 1. Treatment principles and techniques for skeletally immature patients with central, contained OCD lesions occupying 33% width of the capitellum with varying articular cartilage and subchondral bone involvement. (FT = full-thickness; TD = trap-door)